Statin Therapy in Very Old Patients: Lights and Shadows - Cobos-Palacios, Lidia; Sanz-Cánovas, Jaime; Muñoz-Ubeda, Mónica; Lopez-Carmona, María Dolores; Perez-Belmonte, Luis Miguel; Lopez-Sampalo, Almudena; Gomez-Huelgas, Ricardo; Bernal-Lopez, Maria Rosa (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerotic cardiovascular diseases (ASCVD) are the leading cause of death worldwide. High levels of total cholesterol—and of low-density lipoprotein cholesterol in particular—are one of the main risk factors associated with ASCVD. Statins are first-line treatment for hypercholesterolemia and have been proven to reduce major vascular events in adults with and without underlying ASCVD. Findings in the literature show that statins reduce coronary and cerebrovascular morbidity and mortality in middle-aged people, but their benefits in older adults are not as well-established, especially in primary prevention. Furthermore, many particularities must be considered regarding their use in old subjects, such as age-related changes in pharmacokinetics and pharmacodynamics, comorbidities, polypharmacy, and frailty, which decrease the safety and efficacy of statins in this population. Myopathy and a possible higher risk of falling along with cognitive decline are classic concerns for physicians when considering statin use in the very old. Additionally, some studies suggest that the relative risk for coronary events and cardiovascular mortality associated with high levels of cholesterol decreases after age 70, making the role of statins unclear. On the other hand, ASCVD are one of the most important causes of disability in old subjects, so cardiovascular prevention is of particular interest in this population in order to preserve functional status. This review aims to gather the current available evidence on the efficacy and safety of statin use in very old patients in both primary and secondary prevention.